PUBLIC PERCEPTION OF AMIL ZAKAT INSTITUTIONS IN INDONESIA: INSIGHT DISCOVERY FROM MACHINE LEARNING - Timur, Yan Putra; Ratnasari, Ririn Tri; Pitchay, Anwar Allah; Jamilu, Usman (Universitas Airlangga, 2023)
This study aims to identify the most popular topics and words in conversations on Twitter with the topic of Amil Zakat in Indonesia. This research also aims to identify the sentiments and emotions of netizens about the Amil Zakat in Indonesia. This study uses a qualitative method with a sentiment analysis approach with the help of Orange Data Mining. The data used are tweets from Twitter taken from 16 to 23 April 2023. Researchers used the keywords